Colonialism as Foreign Aid: Australian Developmental Policy in Papua New Guinea, 1945–75. Issue 4 (1st October 2020) - Ferns, Nicholas
Abstract : In the three decades following World War II, Australian assistance to Papua New Guinea (PNG) comprised around 80 per cent of the Australian 'aid' budget. The large amount of colonial spending has led many observers of contemporary Australian policy to reflect on the 1960s as a time of Australian generosity in the field of foreign aid. Examining this history through the prism of Australian colonial policy complicates the story of Australian generosity. From the immediate postwar challenges of Eddie Ward's 'New Deal' to the Paul Hasluck period and the immense changes of the 1960s and 1970s, foreign aid and colonial development were inherently (if not explicitly) linked. By bringing these fields of policy together, this article demonstrates that the narrative of Australian foreign aid generosity is challenged by the historical imperatives of colonial administration.